Kwanzaa! : Africa lives in a New World festival - Wilson, Sule Greg. (New York : Rosen Pub. Group, 1999)
Discusses the history, observance, and significance of the African American holiday Kwanzaa.
Includes bibliographical references (p. 62) and index.
Keywords: Kwanzaa -- Juvenile literature; African Americans -- Social life and customs -- Juvenile literature; Kwanzaa; Holidays; African Americans -- Social life and customs